Impaired peripheral reaching and on-line corrections in patient DF: Optic ataxia with visual form agnosia. (January 2018) - Rossit, Stéphanie; Harvey, Monika; Butler, Stephen H.; Szymanek, Larissa; Morand, Stéphanie; Monaco, Simona; McIntosh, Robert D.
Abstract: An influential model of vision suggests the presence of two visual streams within the brain: a dorsal occipito-parietal stream which mediates action and a ventral occipito-temporal stream which mediates perception. One of the cornerstones of this model is DF, a patient with visual form agnosia following bilateral ventral stream lesions. Despite her inability to identify and distinguish visual stimuli, DF can still use visual information to control her hand actions towards these stimuli. These observations have been widely interpreted as demonstrating a double dissociation from optic ataxia, a condition observed after bilateral dorsal stream damage in which patients are unable to act towards objects that they can recognize. In Experiment 1, we investigated how patient DF performed on the classical diagnostic task for optic ataxia, reaching in central and peripheral vision. We replicated recent findings that DF is remarkably inaccurate when reaching to peripheral targets, but not when reaching in free vision. In addition we present new evidence that her peripheral reaching errors follow the optic ataxia pattern increasing with target eccentricity and being biased towards fixation. In Experiments 2 and 3, for the first time we examined DF's on-line control of reaching using a double-step paradigm in fixation-controlled and free-vision versions of the task. DF was impaired when performing fast on-line corrections on all conditions tested, similarly to optic ataxia patients. Our findings question the long-standing assumption that DF's dorsal visual stream is functionally intact and that her on-line visuomotor control is spared. In contrast, in addition to visual form agnosia, DF also has visuomotor symptoms of optic ataxia which are most likely explained by bilateral damage to the superior parietal-occipital cortex (SPOC). We thus conclude that patient DF can no longer be considered as an appropriate single-case model for testing the neural basis of perception and action dissociations.